2020
DOI: 10.1097/dbp.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to Autism Spectrum Disorder Diagnostic Consultation in Rural and Underserved Communities: Streamlined Evaluation Within Primary Care

Abstract: Objective: Preliminary feasibility and clinical utility research has demonstrated that implementation of a streamlined diagnostic model embedded within primary care clinics promotes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Additional research has revealed promising utility for an extended age range of 14 to 47 months. 26,40,41 , and local community organizations (n = 60). Medical presentations were delivered at 73 events (see Fig 1A).…”
Section: Eae Hub Clinical Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…Additional research has revealed promising utility for an extended age range of 14 to 47 months. 26,40,41 , and local community organizations (n = 60). Medical presentations were delivered at 73 events (see Fig 1A).…”
Section: Eae Hub Clinical Pathwaymentioning
confidence: 99%
“…Across the EAE Hubs, the mean age at evaluation was 30 months (see Table 3), significantly less than the national average of 4 to 5 years of age 8 and consistent with existing reports of community-based diagnostic models. [24][25][26][27] Compared to historical 9-to 12-month wait times estimated across tertiary outpatient clinics, the median latency from referral to EAE Hub evaluation (ie, wait time) was 62 days. This finding of improved access through implementation of ASD evaluation in the primary care setting has been found across several smaller studies.…”
Section: Eae Hub Clinical Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, there appears to be a sizeable portion of young children for whom marked social communication impairments and restrictive and repetitive behaviors clearly indicative of ASD can be accurately recognized in a variety of community settings. In addition, these novel assessment models may be quite capable of identifying children who ultimately need more specialized assessments to resolve ambiguity, identified either on review of the initial referral or following a community evaluation (Hine et al, 2020; Mazurek et al, 2019). In these contexts, such expert evaluation can represent an important ‘safety net’ that can mitigate against misclassification.…”
Section: Understanding and Embracing Heterogeneitymentioning
confidence: 99%